(untitled) (MCIT: Proceedings of International scientific and practical conference, 2025)
By focusing on computational tools, the present report shows how it is possible to improve awa- reness of what the educational task is intended to achieve, and it describes the correct methodological foundations and appropriate approach for carrying out a designed digital task. Practical examples de- monstrate important research points: a variety of data storage issues and the technical topic of relation- al databases. A digital education resource that demonstrates how data technologies are used to accom- plish tasks in a research environment. It analyses enabling factors that can support quality, equity and efficiency in the use of digital technologies in education systems. A program of digital research in ed- ucational practice can be characterized as an attempt to marry the interpretation of possible worlds of logic with probabilistic reasoning. It can be said that the discussed concept stands out as one of the most fundamental contributions of information theory to the practice of digital education and is clearly relevant for a number of technical issues, such as the inductive logarithm problem.